Eco-plant polybag (formulation of biodegradable and compostable polybag for soil conditioner) - Wan Nur Fatihah, Wan Abu Bakar; Nurul Aini, Mohd Azman (2021)
Eco-friendly polybag has ability to protect agricultural land and maintain soil fertility. The objectives are to determine biodegradability of eco-friendly polybag in soil burial degradation and compostability of film in chili plant. Eco-friendly polybag were analysed with various formulation consists of refined and semi-refined carrageenan, glycerol, and cellulose nanofiber for their biodegradability and compostability potential